Politics of Notables versus National Machine: Social, Political and State Transformations, Party Organizations and Clientelism during AKP Governments - Toygar Sinan Baykan; Murat Somer (European Journal of Turkish Studies)
This article reviews the existing body of scholarship and draws on original qualitative research that compares the party organizations of four major Turkish parties. By doing so, it highlights the causal relationships -mediated by political agency– between socioeconomic structures and party politics. Clientelism remained part and parcel of Turkish party politics and state-society relations since the transition to multi-party system in mid-20th century through AKP governments. However, important changes occurred in terms of who effectively supplied it, how, and to whom on the basis of broader socioeconomic transformations of Turkey. Political parties did not equally or homologously adjust and respond to social change. The AKP’s successful organizational responses to socioeconomic transformations had important implications for Turkey’s political regime. In pre-AKP clientelism, the state and powerful local notables within parties were key to the supply and distribution of clientelistic benefits. We argue that this contributed to the emergence of electoral democracy under tutelage of military-bureaucratic state actors who faced weak resistance from a fragmented civilian political class. In turn, during AKP governments, the locus of patronage shifted from state to party and from local notables to the AKP party machine: national machine politics. This helped the party to pacify military-bureaucratic tutelage and achieve dominance in party politics, but, the lack of a categorically pro-democratic party ideology and the paradoxes of national machine politics together led the party to transform Turkey to an electoral autocracy instead of developing democracy. Further, the AKP reshaped the Turkish state, which on the surface began to look like a party-state. By revising and providing nuance to this observation, we discuss the emergence of a popular broker-state mediating between national and local state institutions and local communities through its control over resources. We maintain that all these changes facilitated also the party’s internal decay. This generates important opportunities for opposition parties, who however continue to rely heavily on pre-AKP forms of clientelistic politics. Without refashioning their party organizations and party-voter linkages, they may not be able to defeat the AKP electorally, and even if they are, they may not be able to secure successful democratization. They also face difficulties of altering how they form clientelistic linkages with society without controlling state resources at national level.